Analysis Of Marketing Strategies At Trisakti School Of Management Library - Yusrizal, Muhammad; Haromain Al Fashli, Saif; Rahmi, Rahmi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2024)
This study aims to identify and analyze the marketing strategies implemented by the Trisakti School of Management (TSM) Library to enhance service quality and user satisfaction. Utilizing a qualitative approach with a case study method, the research offers in-depth insights through field observations, interviews with library staff, and document analysis. The findings reveal that TSM Library excels in high-quality imported book collections, comprehensive digital resources, and strategically located services. However, challenges include limited reading space and restricted operating hours. The segmentation, targeting, and positioning analysis demonstrates the library's ability to meet the diverse needs of various user groups through focused strategies. The application of the marketing mix (7P) has successfully improved promotional effectiveness and service quality. Social media strategies targeted at Gen Z and Gen Alpha students positively impacted follower growth and user engagement. This study concludes that TSM Library's marketing strategies have positively contributed to service quality and user satisfaction. Recommendations include optimizing physical facilities and expanding promotional programs to reach a broader audience.